PENDIDIKAN ISLAM DAN MODERNITAS DI TIMUR TENGAH: STUDI KASUS MESIR - Ihsan, Muhammad (State Institute of Islamic Studies (IAIN) Palu, 2007)
This article deals with Islamic education and modernity in the Middle East. Modern education began to be known in Egypt since the advent of Napoleon Bonaparte in the early 19th century in this country. However, it was in the epoch of Muhammad Ali that the transision from traditional education to modern education began. Further, in the time of Ismail Pasya due to education reorganization, traditional education began to compete with secular-modern education.Kata Kunci: Pendidikan Islam, modernitas, sekolah modern, Timur Tengah